(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
In this study, the current reality of decapoda living in Syrian freshwater was reviewed. This review aims to update the geographical distribution of species in Syrian freshwater and to provide a map of the distribution of each species, accurately characterizing the species and defining the distinctive characteristics of each of them and possible taxonomic disturbances. There are currently 8 species of crustaceans Decapoda in freshwater in Syria belonging to 5 genera, which in turn represent 4 different species. Of these, four are freshwater cancers of one genus, Potamon, and the other four are freshwater shrimps and belong to four different genera. This review could provide the basic scientific basis for the group of decapoda freshwater in order to continue the study and register new species, and help in developing management strategies to better protect the environments of these species facing increasing human impacts.